Beyond the limelight of Apo Whang-od: Exposing the face of social service delivery and access of older persons in the Philippines - Climson, Balangue (Magyar Gerontológia, 2023)
This study examined the access to social services for the elderly population in Tinglayan, Kalinga, Philippines, which is the home of Apo Whang-od, a globally renowned traditional tattoo artist. The case study explored the challenges and opportunities that elderly individuals encounter in accessing social services within geographically isolated and disadvantaged areas (GIDA) and how these dynamics have been influenced by the artist's popularity.